ANALYSIS OF THE RELATIONSHIP BETWEEN DEGREE OF BLOOD OXYGENATION AND BACKSCATTERED RADIATION WITH THE USE OF NUMERICAL MODELING - O. D. Kozyreva; A. E. Pushkareva; E. V. Shalobaev; I. Biro (Научно-технический вестник информационных технологий, механики и оптики, 2015)
A key role in measuring the level of blood oxygenation is played by a dependence of the signal being measured on the wavelength at which measurements are performed. This paper presents a study of the blood oxygenation effect on the signal of diffusely scattered radiation in the range of 590-860 nm wavelengths. On the basis of previous studies the spectral characteristic of backscattered signal for different levels of blood oxygenation was obtained by the Monte Carlo modeling. In this model photon is characterized by coordinates and weight. The size, step and direction of photon motion from the initial point are determined at each step and specified by means of the random number generator. At each step the photon loses some weight due to absorption. Reducing of the photon weight is also taken into consideration as a result of Fresnel reflection and total internal reflection at two media borderland (the air and blood). The optimal wavelengths range for application in oximeters for sufficiently accurate non-contact measurements of blood oxygenation level by detecting scattered radiation is 650-750 nm. The adequacy of suggested model has been tested by comparing calculated characteristic with experimental results obtained by means of double integral sphere. The highest relative backscattered signal (0.17-0.21) is recorded at 700 nm.